Analysis of readmissions after transoral robotic surgery for oropharyngeal squamous cell carcinoma. Issue 11 (13th August 2018) - Parhar, Harman S.; Gausden, Elizabeth; Patel, Jayendrakumar; Prisman, Eitan; Anderson, Donald W.; Durham, J. Scott; Rush, Barret
Abstract: Background: As transoral robotic surgery (TORS) is being increasingly used to treat patients with oropharyngeal squamous cell carcinoma (OPSCC), there is an interest in determining contributors to readmission. Methods: We conducted this retrospective multivariate analysis modeling 30‐day readmission using the Nationwide Readmissions Database (2012–2014). Results: Of 950 patients, 117 (12.3%) were readmitted. Hemorrhage and diet/aspiration accounted for 32.5% and 19.7% of readmissions, respectively. Of those readmitted, 23.1% required operative bleeding control, 11.1% required transfusion, 1.7% required tracheostomy, and 18.8% required gastrostomies. Those readmitted were older (mean 63.2 years, SD 9.5 vs 60.9 mean years, SD 10.3) and had longer hospitalizations (mean 5.7 days, SD 6.8 vs mean 4.3 days, SD 4.1) and higher rates of aspiration/pneumonia (9.4% vs 2.4%, P < .01) on index admission. Multivariate analysis demonstrated that aspiration/pneumonia on index admission was independently associated with readmission (OR 3.128, 95% CI 1.178‐8.302). Conclusions: Of the patients 12.3% were readmitted within 30 days with hemorrhage and diet complications as significant contributors.